Financial Risk Management Via Evaluating Impacts of a Six Factor Model on LAF Stock Price – A Case in Export Processing Industry in Vietnam - MANH, PHAM TIEN; HUONG, TRAN THI THU (The journal of contemporary issues in business and government, 2021)
Better management of listed firms will help them to attract more FDI investment capitals. There are many factors affecting business management including financial risk management. This papers mainly uses quantitative analysis with OLS model, and qualitative analysis including synthesis, inductive and analytical methods. OLS regression give us results that, in a 6 factors model, LAF stock price decrease are much affected by increase in CPI and lending rate with a significant effect, then increasing the exchange rate. From that, we can have policy and management implications. The limitation of research is that we can expand model for other industries and markets.